REPRESENTASI IDEOLOGI DALAM PEMILIHAN DIKSI BERITA POLITIK DI MEDIA MASSA DARING - Nur Lailiyah; Meyta Lusiana; Dewi Lestari; Awalludin Awalludin (Universitas Muhammadiyah Surabaya, 2026)
This study aims to reveal the ideological representation hidden behind the choice of diction in political news in online mass media. This study is motivated by the fact that language is not only a communication tool, but also a means to shape and convey certain ideologies. This study uses a qualitative approach with Fairclough's critical discourse analysis method that focuses on the relationship between language, power, and ideology. The data is in the form of political news quotes taken from three online mass media with different political leanings. The results show that the choice of diction used in political news is not neutral, but contains ideological tendencies that represent partisanship towards certain political groups. Certain diction is used to present figures or events in a positive or negative image, which indirectly affects readers' perceptions. These findings emphasize the importance of critical awareness in consuming media information as well as the need to use objective and fair language in the news.